STATUS RESISTENSI Aedes aegypti PADA KELURAHAN ENDEMIS DAN NON ENDEMIS DB/DBD di KABUPATEN SEMARANG TERHADAP PERMETHRIN 0,25% - Gerson Socrates Eiriyei (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The resistance of Aedesaegypti to permethrintypes insecticides is one of the problems for controlling DHF / DBvector. Aedesaegypti in the city of Semarang and Salatiga adjacent to Semarang Regency has reportedly been resistant to permethrin. This research uses queasy research experiment with method of susceptibility test. It performed on purpose to see the resistance status of Aedesaegypti populations in the DB / DHF endemic villages (Semarang Regency) which immediately adjacent to the city of Semarang and two comparator areas, namely the Karangjati Village comparator (DBD endemic area), Diwak Village (non-endemic area). Data analysis performed using ANOVA showed the highest death average of mosquito on endemic areas 2 i.e. 11.8 (58.8%) and the lowest on the endemic area 1 i.e. 8.1 (40.6%). Based on ANOVA test, there was no difference on the whole resistance status. Under the provisions of the WHO, on the whole mosquito vector origin Semarang regency was resistant to permethrin 0.25% (mortality <80%). It is recommended that the same research was conducted with study on type and content of agriculture insecticides and household insecticides used in the research site.